Evaluation of Lee–Carter model to breast cancer mortality prediction in China and Pakistan - Mubarik, Sumaira; Wang, Fang; Luo, Lisha; Hezam, Kamal; Yu, Chuanhua (Frontiers in Oncology, 2023)
Precise breast cancer mortality projections are necessary for the planning of public health programs as well as healthcare services. A number of methods for predicting mortality using stochastic models have been developed. The success of these models is highly dependent on the patterns shown by mortality data from various diseases and countries. This study illustrates unconventional statistical method for estimating and predicting the mortality risk between early-onset and screen-age/late-onset breast cancer population in China and Pakistan using Lee-Carter model. Study findings reveal that Lee-Carter approach outperformed for breast cancer mortality rate among screen-age/late-onset than the early-onset population in terms of goodness of fit and within and outside forecast accuracy check. Besides, the trend in forecast error was decreasing gradually in the screen-age/late-onset breast cancer population than the early-onset in China and Pakistan. Further, we observed that this approach had provided almost comparable results between early-onset and screen-age/late-onset population in forecast accuracy for more varying mortality behavior over time like in Pakistan. Breast cancer mortality was predicted to increase to 2030 for both early-onset and screen-age/late-onset population in Pakistan, while for China it was expected to decrease in the early-onset population. The Lee-Carter model can be used to estimate breast cancer mortality and so project future life expectancy at birth, especially in the screen-age / late-onset population. As a result, it is suggested that this approach may be useful and convenient for predicting cancer-related mortality even when epidemiological and demographic disease data sets are limited. According to model predictions for breast cancer mortality, improved health facilities for disease diagnosis, control, and prevention are required to reduce the disease's future burden, particularly in less developed countries.